Effects of Rosemary Extracts on Textural and Functional Qualities of Surimi Gel from Striped Catfish (Pangasianodon hypophthalmus) (Sauvage, 1878) during refrigerated storage - Maurya, Pradip K.; Majumdar, Ranendra K.; Saha, Apurba; Dhar, Bahni; Singh, Asem Sanjit (Fishery Technology, 2018)
Effects of aqueous and ethanolic extracts of rosemary leaf on textural and functional properties of surimi gel from striped catfish (Pangasianodon hypophthalmus) (Sauvage, 1878) during refrigerated storage was evaluated. The properties of surimi gel such as gelling, water holding capacity, protein solubility, texture profile, whiteness, as well as the quality indices like total volatile bases and thiobarbituric acid values were estimated periodically during a refrigerated storage period of 20 days. Increase of water holding capacity in rosemary extract added gels indicated stronger protein network formation, whereas, protein solubility decreased significantly in all the groups as the storage progressed indicating the formation of protein aggregates. Thiobarbituric acid value, indicative of lipid oxidation decreased in treated samples but at different rates, depending upon the concentration of rosemary extract. Gel strength of samples was affected upon incorporation of rosemary extract and treated groups showed higher values than the control, indicating the positive role of rosemary’s phenolics in cross linking of protein-protein interaction. Textural attributes were found to be affected most due to addition of rosemary. The control samples tended to have the largest decreasing rate of whiteness during the period of storage, compared to the treated groups (0.25-0.75%). Both the extracts of rosemary at higher concentration (0.75%) showed highest consumer acceptability on day-1 and also at the end of the storage period. On the basis of sensory evaluation the control was acceptable only upto 12 days.